2011
DOI: 10.1136/heartjnl-2011-300102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycosylation on plasma N-terminal proBNP-76 levels in patients with heart or renal failure

Abstract: THE findings suggest that most endogenous plasma NT-BNP is glycosylated and therefore undetectable with the current assay system, and that the relative glycosylation level is increased by haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 31 publications
(43 reference statements)
3
50
0
Order By: Relevance
“…3, C and E). This is supported by the work from Nishikimi et al, who recently reported that the ratios of glycosylated and nonglycosylated forms of plasma NT-proBNP are constant in all HF patients (NYHA class 1-4) (25 ).…”
Section: Discussionsupporting
confidence: 68%
“…3, C and E). This is supported by the work from Nishikimi et al, who recently reported that the ratios of glycosylated and nonglycosylated forms of plasma NT-proBNP are constant in all HF patients (NYHA class 1-4) (25 ).…”
Section: Discussionsupporting
confidence: 68%
“…In previous studies, the Roche Elecsys Gen I detection antibody (aa 39 -50) demonstrated poor cross-reactivity with glycosylated NT-proBNP and this was confirmed in our study (data not shown). A significant increase in plasma NTproBNP concentrations was noted following deglycosylation, suggesting that this assay measures only 20% of circulating NT-proBNP which corresponds to the nonglycosylated form (15,16 ). The Roche Elecsys NTproBNP Gen II assay also uses antibodies directed to the central glycosylated region (aa 42-46) and nearly all NTproBNP assays used clinically use Roche NT-proBNP I or NT-proBNP II antibodies which recognize residues in this highly glycosylated region.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be aware that these detection platforms underestimate the concentration of circulating biomarker considerably. Some studies suggest that the underestimation might be up to 10-fold (19,35 ). Some recommend that future NT-proBNP platforms use deglycosylation of blood samples before assay.…”
Section: Nt-probnp Assaysmentioning
confidence: 99%
“…This study included a blend of chronic and acute HF patients. Reference limits also vary by age and sex of patients analyzed (35 ).…”
Section: Nt-probnp Assaysmentioning
confidence: 99%